Tinjauan Yurisdis Penyelesaian Sengketa Pajak Di Indonesia - Noor Ihsan, Reza; Adisty Indallah, Salsabila; Nazwa Alwisyah, Ahmad; Ningsih, Sartika; Bayu Kencono (Universitas Kapuas, 2024)
Tax dispute resolution is a legal process that aims to resolve disputes between tax authorities and taxpayers regarding disagreements over tax obligations that arise. The administration stage involves negotiation and mediation efforts between the taxpayer and the tax authority with the aim of reaching a settlement agreement. If a settlement is not reached, the taxpayer can appeal to a court or special arbitration body appointed to resolve the dispute. In order to increase the effectiveness of tax dispute resolution, it is important to have a clear and transparent legal framework, as well as develop an efficient and fair process. This study aims to analyze the legal aspects of tax settlement in Indonesia with a normative approach. This study uses analytical methods and the results of the research show the important role of the tax authorities and the judiciary in the process of resolving tax disputes. Keywords: Taxpayers; Tax Authorities; Administration; Litigation.